Sosialisasi Literasi Digital Dalam Meningkatkan Keterampilan Penggunaan Media Digital Bagi Siswa SMPN I Limbangan Garut Pada Abad 21 Sesuai Dengan Profil Pelajar Pancasila - Leni Sri Mulyani; Chevi Ardiana; Sri Mulyaningsih (Puslitbang Akademi Relawan TIK Indonesia (ARTIKA), 2023)
The digital literacy socialization has become an essential aspect of education in the 21st century. Where digital technology plays an increasingly dominant role in everyday life, students need to be equipped with adequate skills to use digital media. These skills are required for better academic achievement and for shaping a generation capable of actively participating in an increasingly digitally interconnected society. The Pancasila student profile emphasizes the importance of building strong character and morals that are relevant to digital literacy. Digital literacy socialization should integrate Pancasila values into the learning process, ensuring that students are not only proficient in technology but also able to use digital media wisely and ethically. In the 21st century, the ability to identify accurate information, avoid the spread of fake news, and engage in healthy online discussions are key skills. Therefore, digital literacy socialization aims to equip students with the knowledge and skills required through a relevant curriculum. This research investigates the impact of digital literacy socialization on students' digital media usage skills in line with the Pancasila student profile. The results of the study indicate that digital literacy socialization is effective in enhancing students' digital media usage skills. This creates a generation capable of using digital technology wisely, respecting Pancasila values, and making a positive contribution to an increasingly digitally interconnected society.